O79 Driving quality in healthcare simulation – applying lean management principles to learning. (5th November 2017) - Sullivan, C; Murray, JM
Abstract : Background: The opening of a state of the art simulation centre at the Royal College of Surgeons Ireland will offer exciting opportunities. With expected footfall of over 4, 000 students annually, it was identified that a robust system would be needed to ensure quality and efficiency of the learning experience and to allow for future expansion. Lean management principles have been successfully applied to education (Emiliani, 2004) and healthcare (Joosten, Bongers, & Janssen, 2009). Simulation is where education and healthcare delivery meet. We propose therefore that lean management principles may guide the successful operation of a healthcare simulation centre. Method: Following a scoping exercise of existing and potential Simulation Based Education (SBE) activities across all RCSI curricula, it became evident that it would be necessary to standardise the delivery of SBE. For each discrete teaching session, a 'toolbox' was developed which contained learning objectives, a standard operating procedure (SOP) for that session and all the necessary artefacts for the learning encounter including consumables. Outcomes: The SOPs allow for the development of a value stream process map which in turn facilitates continual improvement in quality and efficiency. The use of software which facilitates easy collection of video recordings of teaching will allow for transparency, evidence-based video assessment and standardized performance data to learners, faculty, and the centre and assist with ongoing quality improvement in teaching. Conclusion The new centre challenges us to adopt a fresh approach to SBE. The creation of a modular system using lean management principles will enable simplicity, commoditization and performance analysis and support easy quality review and ongoing process improvement. References: . Emiliani ML. Improving business school courses by applying lean principles and practices. Quality Assurance in Education 2004;12(4):13. . Joosten T, Bongers I, Janssen R. Application of lean thinking to health care: issues and observations. Int J Qual Health Care 2009;21(5):341–347. doi: 10.1093/intqhc/mzp036